Social Interactions and Quality of Life among Community-Dwelling Older Adults - Alfianur, Alfianur; Ezalina, Ezalina; Saputra, Candra; Sapitri, Gusdi Riska (Indonesian Journal of Global Health Research, 2024)
The escalating quantity of older individuals as a susceptible demographic necessitates significant consideration. The emergent challenges encompass not solely physical aspects but also psychological and societal dimensions, subsequently impacting their holistic well-being. An element contributing to the enhancement of the well-being of older individuals involves participating in communal exchanges. Past studies have suggested that seniors who regularly partake in various pursuits and participate in favorable social exchanges in their day-to-day routines may enhance their well-being. This study aimed to examine and analyze the relationship between social interaction and the quality of life among community-dwelling older adults. This study was a correlation with a cross-sectional approach. The sample was selected purposively, resulting in a sample of 228 older adults at the Harapan Raya Inpatient Health Center in Pekanbaru City. The data were collected using two validated questionnaire including social interaction questionnaire with Cronbach's α coefficient of 0.882, and WHOQOL-BREF with the Cronbach's α coefficient for the domains ranged from 0.41 to 0.77. To test the hypothesis regarding the relationship between the social interaction and the older adults quality of life, a chi-square test was employed. The research findings revealed a significant relationship between social interaction and the quality of life among older adults, with a p-value of 0.00 (<0.05) and an OR of 5.6. This implies that older adults with high social interaction have a 5.6 times higher chance of experiencing a good quality of life compared to those with low social interaction. Older adults with high social interaction tend to have a better quality of life compared to those with low social interaction.